Habitação popular na cidade capitalista : luta por moradia e MTST em Aracaju - Santos, Joyce Kelly de Jesus (2022)
The emergence of the capitalist mode of production brought about changes in society. The development of industry gave birth to a modern proletariat that arrived in the cities dispossessed to sell their labor power. This process brought impacts to urbanization that began to meet the logic of capital accumulation and needed to incorporate the mass of workers in its dynamics. In the city, there are several contradictions that reflect the capitalist mode of production, housing being one of them. Thus, the process of modern urbanization was permeated by resistance and workers' struggle for the right to housing. Currently in Brazil, the Homeless Workers Movement (MTST) fulfills the role of organizing the struggle for housing in several states and has established itself as the largest social movement in the struggle for housing. The MTST, through its occupations, produces the urban space of the capitalist city in a counter-hegemonic logic to that imposed by capital, since, for this movement, the city, before constituting the space for the reproduction of capital, is where reproduction of life takes place. As a way of fighting to guarantee the right to housing, in 2017, the MTST started its organization in Aracaju/SE, working from the occupations mapped in the North and South Zones of the city. The general objective of this research is to analyze popular housing in the development of the capitalist city. Therefore, in order to unveil the phenomenon of workers' struggle for housing in its connections with the exploitation of the working class and as part of the capitalist social structure, the research is based on historical and dialectical materialism, making use of the geographical category of production of the space. The following methodological paths were adopted: study of theories that corroborated with the foundation of the work, review of the state of the art of the agenda, field research, with the application of semi-structured interviews, mapping of the movement's areas of activity, systematization and analysis of the information collected in the survey. That said, the spatialization of the MTST in Aracaju reveals that the lack of housing is a fact of the material reality in the municipality, present among the poorest and most precarious workers. The occupations are carried out by these workers in poorer areas, which reflects the organization of their social base.